Temporal Variation of Surface Water Quality in the Swan River Catchment in Himachal Pradesh India - Sharda, Avinash Kumar; Sharma, Harish Chander; Bhushan, Brij (Hydro Nepal: Journal of Water, Energy and Environment, 2017)
As industrial growth in the lower Shiwalik hills has risen in past two decades, the last 10 years in the Una district has seen a rapid development in industrial and urban growth due to grant of industrial package by the central government of India. As a result, several production plants have sprung up within the Swan River catchment, threatening the water quality of this area. However, the actual effects on water quality are heretofore unknown. In this paper, we assess the water quality of the Swan River catchment by calculating the National Sanitation Foundation Water Quality Indicators (NSFWQI) and Overall Index of Population (OIP) between 2003-2012. Data on monitored cross sections were collected from State Pollution Control Board of Himachal Pradesh, India. The results indicate that there has been recent (within five years) considerable improvement in the water quality due to enforcement of proper pollution control technologies. The relationship between economic growth (GDP) and water quality was also studied.We carried out regression analysis of the water quality data to determine significant parameters as independent variables and WQI and OIP as dependent variables. The regression analysis further identified that the contribution of each variable with significant values r = 0.733, R2 = 0.695. The study further suggests that sustainable development is possible through adoption of proper treatment technologies, enforcement of formal legislation, and preparation of remedial action plans to reduce the environmental stresses.HYDRO Nepal JournalJournal of Water Energy and EnvironmentIssue: 20Page: 55-61